Intratumoral IL-1R1 expression delineates a distinctive molecular subset with therapeutic resistance in patients with gastric cancer. Issue 2 (2nd February 2022) - Zhang, Puran; Gu, Yun; Fang, Hanji; Cao, Yifan; Wang, Jieti; Liu, Hao; Zhang, Heng; Li, He; He, Hongyong; Li, Ruochen; Lin, Chao; Xu, Jiejie
Abstract : Background: With the essential role of interleukin-1 signaling in cancer-related inflammation, IL-1R1, the main receptor for both IL-1α and IL-1β, demonstrated therapeutic potential in several types of cancer, which has been put into clinical trials. However, the expression profile and critical role of IL-1R1 in gastric cancer (GC) remain obscure. This study aimed to investigate the prognostic significance of IL-1R1 expression and its predictive value for chemotherapy and immunotherapy in GC. Methods: The study enrolled three cohorts, consisting of 409 tumor microarray specimens of GC patients from Zhongshan Hospital, 341 transcriptional data from The Cancer Genome Atlas, and 45 transcriptional data from patients treated with pembrolizumab. IL-1R1 mRNA expression was directly acquired from public datasets, and we also detected IL-1R1 protein expression on tumor microarray by immunohistochemistry. Finally, the associations of IL-1R1 expression with clinical outcomes, immune contexture, and genomic features were analyzed. Results: High IL-1R1 expression predicted poor prognosis and inferior responsiveness to both 5-fluorouracil-based adjuvant chemotherapy (ACT) and immune checkpoint blockade (ICB). IL-1R1 fostered an immunosuppressive microenvironment characterized by upregulated M2 macrophages and exhausted CD8 + T cells infiltration. Moreover, the expression of IL-1R1 was intrinsically linked to genomic alterations associated with targeted therapies in GC. Conclusions: IL-1R1 served as an independent prognosticator and predictive biomarker for ACT and ICB in GC. Furthermore, IL-1R1 antagonists could be a novel agent alone or combined with current therapeutic strategies in GC.